An infodemiology approach to assess the impact of unemployment on anxiety and depression in France. Issue 2 (3rd April 2023) - Ramos-Gomez, Ariadna; Pérez-Escatel, Aldo A.; Villaseñor-García, Elio Atenógenes; Ramos-Remus, Cesar
Abstract: Mental health is a key factor for productivity and an indicator of the general well-being of the population. There has been growing evidence in past years that unemployment negatively affects the mental health of the population and, hence, reduces its overall well-being. This study assesses the unemployment and mental health correlation and, specifically, whether depression and anxiety increased due to the rise in unemployment during the 2009 debt crisis in France. We followed an infodemiology approach by first creating a distress index that accounted for all depression and anxiety-related words. Then, by mobilizing Google Trends data, we used diverse economic- and employment-related datasets for France as covariates in multiple linear regression analyses. This study is one of the first to use broad search terms through a distress index that was not restricted to the words "depression" and "anxiety, " but also considered associated terms that individuals may use when seeking information on depression and anxiety. This is also one of the first studies to introduce an infodemiology approach to health economics in France. The results showed that for each unit of additional demand for unemployment benefit, the search traffic for the distress index increased by 0.09%, a positive increase that was minor. The mild effect of demand for unemployment benefits on the distress index may be explained by aspects of social protection policies in France. This paper includes valuable policy suggestions, whereof policymakers could benefit from.